Pengaruh Wawasan Kevokasionalan Siswa SMP terhadap Minat Melanjutkan di SMK - Ahmad Fathoni; Kholida Ismatullah (Universitas Hamzanwadi, 2018)
The study aims to describe: (1) how much insight into the vocational high school students consists of understanding vocational school as work world education (X1), understanding types of expertise programs (X2), understanding of the work world (X3), and counseling guidance services (X4) towards the interest in continuing in SMK (Y); (2) how much influence is the vocational insight of Grade IX junior high school students consisting of understanding vocational school as work world education (X1), understanding types of expertise programs (X2), understanding of the work world (X3), and counseling guidance service (X4) on interests continue at SMK (Y). Research is a survey research with a quantitative approach. The research sample of 197 students was determined using the proportionate random sampling technique. Data collection used questionnaires, documents, and observations. Data analysis usds descriptive statistics. The results showed that: (1) variables X1, X2, X3, X4 were included in the high category, the variables were good for continuing interest in Vocational Schools; (2) variables X1, X2, X3, X4 have an effect on the variable Y with the correlation coefficient values respectively 0.580, 0.564, 0.479, 0.564 and simultaneous X1, X2, X3, X4 against Y there is an influence with a correlation coefficient of 0.727.